ANALISIS REGRESI LOGISTIK MULTINOMIAL DALAM ESTIMASI PARAMETER KRITIS INDEKS STANDAR PENCEMAR UDARA - Rahmadita Pratiwi; Rina Widyasari; Muhammad Fathonni (LPPM Universitas Bina Bangsa, 2024)
The Air Pollutant Standard Index contains parameters monitored daily, one of which is the critical parameter with the highest pollutant rating among other parameters. The air critical parameters used as dependent variables consist of four categories, namely Carbon Monoxide (????????), Particulate Matter (????????10), Sulfur Dioxide (????????2), and Ozone (????3). In this research, Carbon Monoxide (????????) used as the comparison category and results obtained are variables that affect the Particulate Matter (????????10) category is the air temperature variable with category 0. In the Sulfur Dioxide (????????2) category, the influential variable is wind speed with category 0. And the last category Ozone (????3) influences more independent variables, namely the rainfall variable with category 0, the wind speed type variable with category 0, and air humidity with category 0. The resulting classification accuracy value is quite low at 53%, so it is clear that the classification of the critical parameters of air pollution index is not feasible